On the Wind Turbine Wake and Forest Terrain Interaction - Shyuan Cheng (MDPI AG, 2021)
Future wind power developments may be located in complex topographic and harsh environments; forests are one type of complex terrain that offers untapped potential for wind energy. A detailed analysis of the unsteady interaction between wind turbines and the distinct boundary layers from those terrains is necessary to ensure optimized design, operation, and life span of wind turbines and wind farms. Here, laboratory experiments were carried to explore the interaction between the wake of a horizontal-axis model wind turbine and the boundary layer flow over forest-like canopies and the modulation of forest density in the turbulent exchange. The case of the turbine in a canonical boundary layer is included for selected comparison. The experiments were performed in a wind tunnel fully covered with tree models of height <semantics>H/zhub≈0.36</semantics>, where <semantics>zhub</semantics> is the turbine hub height, which were placed in a staggered pattern sharing streamwise and transverse spacing of <semantics>Δx/dc=1.3</semantics> and 2.7, where <semantics>dc</semantics> is the mean crown diameter of the trees. Particle image velocimetry is used to characterize the incoming flow and three fields of view in the turbine wake within <semantics>x/dT∈(2,<mspace width="4pt"></mspace>7)</semantics> and covering the vertical extent of the wake. The results show a significant modulation of the forest-like canopies on the wake statistics relative to a case without forest canopies. Forest density did not induce dominant effects on the bulk features of the wake; however, a faster flow recovery, particularly in the intermediate wake, occurred with the case with less dense forest. Decomposition of the kinematic shear stress using a hyperbolic hole in the quadrant analysis reveals a substantial effect sufficiently away from the canopy top with sweep-dominated events that differentiate from ejection-dominated observed in canonical boundary layers. The comparatively high background turbulence induced by the forest reduced the modulation of the rotor in the wake; the quadrant fraction distribution in the intermediate wake exhibited similar features of the associated incoming flow.